(untitled) (Research, Society and Development, 2022)
Objective: to identify the challenges of implementing the National Policy for Comprehensive Attention to Men’s Health, in Mato Grosso. Methodology: integrative literature review of publications from 2012 to December 2020, in CAPES, MEDLINE, LILACS, SciELO and Academic Google databases. Results: 17 articles were selected for this work. The challenges identified in the implementation of the policy are related to: obstacles in the consolidation of the policy, cultural aspects of gender/masculinity, continuing education and training for health professionals, the hours of operation of the units and few educational actions aimed at this population. Conclusion: the permanent training of health professionals in Primary Care aiming at the practice of specific activities in accordance with the policy guidelines, the organization and performance of strategic activities, easily accessible to men, in addition to the adequacy of the hours of operation in the units, becomes fundamental for their awareness and adherence.